Utilization of Prototyping Models in Designing User Interfaces for Learning Applications for Preparation of Medical Records Competency Tests (PERKOMDIS) - Darmawan, Mochammad Arief; Wijayanta, Setya; Sugiarto, Puput (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Designing a good user interface is crucial in designing digital-based learning applications, one of which is to support student readiness for the Medical Records and Health Information Competency Test (UKOM). This study aims to utilize a prototyping model to design the user interface for the Medical Records and Health Information Competency Test Preparation Learning (PERKOMDIS) application. This application interface design is an interactive mobile app-based learning medium. The prototyping model allows for interactive user interface design by involving users in analyzing initial requirements. The study was conducted through several stages: user needs analysis, user interface design, and display feasibility testing by potential users. The results showed that the use of an interactive prototyping model improved the quality of the interface design, both in terms of usability, navigation clarity, and visual appeal. The PERKOMDIS application is designed to include practice questions, material discussion, and self-assessment features integrated into a single platform. With a user-focused approach and the implementation of competency-oriented design, this user interface design is expected to be an effective tool in the process of developing a UKOM preparation application for Medical Records and Health Information students.